BIOREGIONALISM: A PATHWAY TO ECO- SUSTENENCE - PANSY EVANGELINE VICTOR , L. JENNIFFER , Dr. K.CHARLES GODWIN (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The theory of Bioregionlism thrives to construct values of justice, freedom, equality and liberty to understand the region of 'one's dwelling place' in the vast expanse of the biosphere. It creates a strong bond between human and nature. Every component of the ecological world travels in separate ways to built 'one earth' and 'one future'. It stresses upon the diversities of human's behaviour. The theory of bioregionalism emphasises that the task of the human world is to understand one's territory, including its change of seasons, land, water sources and nature's bounty of one's particular region. The theory voices that it one's responsibility to know Literature takes us to the past, lives in the present and will continue to live for generations. Every region has its history of tradition, culture, food, farmlands etc. As nature and society are akin to each other, the theory of bioregionalism urges to study every layer of the particular region. The paper voices about the power of nature. The ecological aspects of the mother earth is documented day after day. Nature never fades, it will continue to create unfathomable histories. Nature holds moral, spiritual and aesthetic values. The article focuses on the concept of bioregionalism. Articles from newspapers and magazine are included for better understanding. Human and nature are integrated in a complex web but, it lives as "a true community in which all creatures and all things can be felt as brother and sisters ( Mulvaney 82)". The article voices that, all the human and non-human beings should be treated with respect and reverence as all living beings hold a part of life as breathing. To create a better future, the human world should stay positive, energetic and realistic. It conveys to the human world to have the goal to stand united with 'community feeling' to recreate the lost green world.